Pituitary Stalk Stretch Predicts Postoperative Diabetes Insipidus After Pituitary Macroadenoma Transsphenoidal Resection. Issue 3 (10th March 2023) - Hoang, Alex Nguyen; McGahan, Benjamin G.; Cua, Santino; Magill, Stephen T.; Nayak, Pratima; Montaser, Alaa S.; Ghalib, Luma; Prevedello, Luciano M.; Hardesty, Douglas A.; Carrau, Ricardo L.; Prevedello, Daniel M.
Abstract : BACKGROUND: Manipulation of the pituitary stalk, posterior pituitary gland, and hypothalamus during transsphenoidal pituitary adenoma resection can cause disruption of water electrolyte regulation leading to diabetes insipidus (DI). OBJECTIVE: To determine whether pituitary stalk stretch is an independent risk factor for postoperative DI after pituitary adenoma resection. METHODS: A retrospective review was performed of patients undergoing endoscopic endonasal resection of pituitary macroadenoma between July 2010 and December 2016 by a single neurosurgeon. We analyzed preoperative and postoperative imaging metrics to assess predictors for postoperative DI. RESULTS: Of the 234 patients undergoing resection, 41 (17.5%) developed postoperative DI. DI was permanent in 10 (4.3%) and transient in 31 (13.2%). The pituitary stalk stretch, measured as the change in stalk length from preoperative to postoperative imaging, was greater in the DI compared with the non-DI group (10.1 mm vs 5.9 mm, P < .0001). The pituitary stalk stretch was associated with DI with significant difference in mean pituitary stalk stretch between non-DI group vs DI group (5.9 mm vs 10.1 mm, P < .0001). Multivariate analysis revealed that pituitary stalk stretch >10 mm was a significant independent predictor of postoperative DI [odds ratios = 2.56 (1.10-5.96), P = .029]. When stratified into transient and permanent DI, multivariable analysis showed that pituitary stalk stretch >10 mm was a significant independent predictor of transient DI [odds ratios = 2.71 (1.0-7.1), P = .046] but not permanent DI. CONCLUSION: Postoperative pituitary stalk stretch after transsphenoidal pituitary adenoma surgery is an important factor for postoperative DI. We propose a reconstruction strategy to mitigate stalk stretch.